Implementing Positive Discipline to Enhance Character Education in High Schools - Khasbiyah, Ani; Apriani, Dewi; Basukiyatno (Research Horizon, 2025)
Education plays a crucial role in shaping students’ character, fostering traits like responsibility, discipline, and independence, beyond mere knowledge transfer. However, issues such as rule violations and lack of self-awareness among students highlight the need for effective character education strategies. This study aims to examine how positive discipline, a humanistic approach emphasizing self-awareness and responsibility without physical or verbal punishment, strengthens character education in high schools. Using a descriptive qualitative literature review, data were collected from journal articles, academic books, and official education reports. The findings indicate that positive discipline reduces disciplinary violations, enhances moral awareness, and creates a safe, inclusive school environment. Key supporting factors include consistent teacher practices, parental involvement, and a collaborative school culture, though challenges like punitive mindsets, time constraints, and low student awareness persist. The study concludes that positive discipline significantly enhances character education by promoting responsibility, independence, and moral integrity, offering a sustainable approach to cultivating well-rounded students. It provides practical strategies for schools to foster discipline humanely, aligning with national education goals to develop virtuous and skilled individuals, with potential to elevate character development to an excellent level.